CJEU Standards of Proof in Cases of EU Targeted Human Rights Sanctions : An assessment of CJEU’s current standards of proof in EU targeted sanctions regimes, prospects for development through the future case law of EU Global Human Rights Sanctions Regime and concerns relating to the respect of the principle of legal certainty - Roos, Nina (My University, 2022)
With the first two decades of the 21st century marked by increasing political tensions and democratic crisis, the EU has risen to the occasion by assuming the position of a major foreign policy actor. Possessing a broad repertoire or foreign policy tools, the EU strives to uphold and advance its core values, including the human rights and fundamental freedoms, stated in Article 21 TEU. One foreign policy tool, namely, sanctions measures, have become widely used, resulting in added scrutiny on the functioning of this tool. With criticism on the negative humanitarian effects and perceived ineffectiveness of traditional state-focused sanctions measures, the EU has implemented targeted sanctions regimes with the most recent, the EU Global Human Rights Sanctions Regime, being adopted on the 7th of December 2020 through Council Decision 2020/1999 and Council Regulation 2020/1998. Although the targeted nature of sanctions has reduced the broad negative effects on civilians, it has simultaneously created new issues which remain unsolved. This study uses the recently adopted EU targeted human rights sanctions regime to discuss issues of the CJEU’s evidentiary standards in targeted sanctions cases. The aim of this study is to establish, 1) whether targeted human rights sanctions measures could have the character of criminally natured administrative sanctions, 2) what role standards of proof have in the Court’s evaluation of targeted human rights sanctions cases, and, and 3) whether there could be concerns of the respect of the principle of legal certainty in this context. The study is based on a legal dogmatic approach but utilizes also elements of comparative and problem-oriented approaches. The comparative approach of this study have been narrowed to the case law of the European Court of Human Rights, case law from the area of EU Competition law as well as some references to the UN Sanctions Regimes. While there are some valid concerns on how the CJEU reviews evidence in targeted sanctions cases, the broadness and vagueness of EU standards of proof could be explained through the civil law legal traditions of the CJEU. It seems as though a natural way forward would be for the CJEU to adopt similar processes in targeted sanctions cases as it has done through competition law. Similarly, the direction from ECtHR case law could also be used to further develop the area of EU targeted sanctions.

Poliittisten kriisien alati lisääntyessä 2000-luvun aikana, EU on omaksunut merkittävän roolin ulkopoliittisena toimijana. EU:lla on laaja valikoima ulkopoliittisia välineitä, joilla se pyrkii ylläpitämään ja edistämään SEU-sopimuksen 21 Artiklassa määrittelyjä arvoja, mukaan lukien ihmis- ja perusoikeuksia. Yksi ulkopoliittinen väline, nimittäin pakotetoimenpiteet, ovat yleistyneet huomattavasti, lisäten niihin kohdistuvaa keskustelua ja kritiikkiä. Vastareaktiona perinteisten valtiokeskeisten pakotetoimenpiteiden negatiivisille humanitaarisille vaikutuksille ja koetulle tehottomuudelle, EU on luonut kohdennettuja pakotejärjestelmiä, joista viimeisin, EU:n globaali ihmisoikeuspakotejärjestelmä on pantu täytäntöön 7.12.2020 neuvoston päätöksen 2020/1999 ja neuvoston asetuksen 2020/1998 myötä. Vaikka pakotteiden kohdennettu luonne on vähentänyt niiden laajoja kielteisiä vaikutuksia siviileihin, ovat ne samalla nostaneet esille uusia ongelmakohtia, joihin ei vielä ole vastauksia. Tämä tutkimus käyttää hiljattain hyväksyttyä EU:n kohdennettua ihmisoikeuspakotejärjestelmää keskustellakseen EUT:n näyttökynnykseen liittyviä haasteita kohdistetuissa pakotetapauksissa. Tutkimus pyrkii selvittämään, 1) voisivatko kohdennetut ihmisoikeuspakotteet olla luonteeltaan rikosoikeudellisia hallinnollisia seuraamuksia, 2) takaavatko EU:n tuomioistuimen nykyiset näyttökynnykset pakotekohteiden prosessuaaliset oikeudet riittävissä määrin, ja 3) onko tässä yhteydessä aihetta epäillä oikeusvarmuuden periaatteen loukkauksia. Tutkimus perustuu oikeusdogmaattiseen lähestymistapaan, mutta hyödyntää myös vertailevaa ja ongelmalähtöistä lähestymistapaa. Tutkimuksen vertailevat aspektit on rajattu Euroopan ihmisoikeustuomioistuimen oikeuskäytäntöön, EU:n kilpailuoikeuden alaa koskevaan oikeuskäytäntöön, sekä tiettyihin viittauksiin YK:n pakotejärjestelmiin. Vaikka huoli EUT:n tavasta toimia näyttökysymyksissä on perusteltua, näyttäisi EU:n näyttökynnyksen laajuus ja epämääräisyys viestimään pikemminkin EU:n siviilioikeudellisesta oikeusperinteistä kuin perusoikeudellisista ongelmista. Tutkimus esittää, että EUT:n kohdennettujen pakotetapausten luonnollinen kehittymissuunta, olisi seurata EU:n kilpailuoikeudessa omaksuttuja käytäntöjä. Sama koskee Euroopan ihmisoikeustuomioistuimen oikeuskäytäntöä kohdennettujen pakotteiden alueella.
Keywords: EU Law, Court of Justice of the European Union, Council of the European Union, Common Foreign and Security Policy, targeted sanctions, standard of proof, procedural rights, human rights, counter-terrorism sanctions, competition law sanctions, principle of legal certainty.